Reframing Library Budgeting Through Zero-Based Budgeting Models - Suneetha, K.; Jahanara, Umme; Sudan, Prerak; Singh, Subhi; Samantaray, Priyambada; Vasantha, S.V. (Indian Journal of Information Sources and Services, 2026)
Typically, library budgeting uses incremental funding increases that tend to simply evolve budgets from the previous year without consideration of evolving patron needs, technology changes, or programmatic needs of equity and access. This article looks backwards on the construct of incremental budgeting and forward to the possibility of using Zero Based Budgeting (ZBB) as a prospective planning approach for public and academic libraries. Zero-based budgeting requires departments to begin from scratch with each budget period, requiring each proposed expense to be justified in relation to the institution’s strategic priorities, demonstrate value delivery in services, and model measurable impacts. The research examines the practice of zero-based budgeting in higher education libraries with a review of several controlled simulations and by observation of institutional examples from different universities. The result of the analysis yielded four additional benefits- more transparency of the budget process; termination of unneeded budget lines; enhanced correlation between budget lines and legitimate user needs; and accelerated institutional response to unanticipated mid-year changes in budgeting. The modifications to the zero-based budget plan prototype provide discrete cost centres with a footprint around an institution’s mission, uses multi-dimensional criteria to justify each expense, and adapts user-impact scoring techniques that align with, and in every case reside in the original strategic plans of the institution. Interviews with key budget stakeholders and electronically administered surveys provide qualitative perspectives that suggest considerable increases in confidence about budget sustainability, a stronger culture of stewardship, and broader participation from an increasingly diverse pool of constituents in deliberative budget discussions. Together, these perspectives re-frame zero-based budgeting as more than just a tool for controlling costs; they frame it as a forward-looking framework that distributes services equitably, manages pilot projects, and ensures the sustainability of library service in the long term. This emphasizes a new forward orientation of adaptive budget processes that can respond quickly to emerging community priorities, an ability that is grounded in empirical proof-of-concept and co-developed by a robust, continuously engaged, diverse network of stakeholders. Here, ZBB is a reasonable, future-proof strategy that can allow libraries to work within tight budgetary constraints, while continuing to develop and deliver services that have a meaningful, quantifiable social impact.